Pendidikan Seni yang Humanis dengan Pembaharuan Pendidikan dan Pembelajaran melalui Penanaman Empat Pilar Pendidikan - Ardipal Ardipal (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2010)
The goal of humanistic art education is to build a conducive atmosphere for learning and learning activities as self-exploration activities. To develop the potential of the learners, the renewal of education and learning for the sake of increasing the professionalism of educators is needed. Therefore, improvement of professional skills education should be directed at fostering professional skills as well as coaching commitments. The improvement of professional capacity of educators through the concept of educational reform is more directed to cultured education and grown as a whole. Key words: Art Education, Humanistic